Site Determination of Decision Support System Pelita Nusantara STMIK Campus Branch With the Electre Method - Santiwati Sihotang; Hengki Tamando Sihotang (Institute of Computer Science (IOCS), 2020)
The problem that is often faced by the campus is ineffective in determining strategic locations. Failure to determine the location will be detrimental to the campus, resulting in the closure of the campus. To avoid this problem, analysis and appropriate methods are needed to assist in determining strategic campus locations. The Electre method is a decision-making method based on the Outranking concept that produces various alternatives to assist management in dealing with structured and unstructured problems, based on pairwise comparisons with alternatives that match the criteria and those that do not match the criteria will be eliminated. This method is needed as a Decision Support System (SPK) that can help the STMIK Pelita Nusantara campus, Medan in determining strategic campus locations. This study aims to apply the Electre method and build a Decision Support System for determining the location of the STMIK Pelita Nusantara branch campus. The method used in this study is the electre method to determine Population Density weighting, transportation access, location security, distance to other campuses, and high school / vocational school level education. Based on the analysis using the electro method, it is known that the strategic location of the campus branch can be used as an alternative, namely Medan Johor